Correlation Between Nutritional Knowledge and Behaviour of Implementing Vegetable and Fruit Consumption with Nutritional Status of Bhayangkara University Bekasi Students - Tazhkia, Nurarifah; Noerfitri, Noerfitri (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: In Indonesia, there are still many problems with nutritional status in adulthood. College students are entering the adult phase. Factors that affect nutritional status are nutritional knowledge and food intake. Individual nutritional knowledge affects behaviour in food selection. Meanwhile, high fiber food intake in adulthood is important for maintaining a healthy body. High fiber content is found in vegetables and fruits. This study aims to analyze the relationship between the level of nutritional knowledge related to vegetables and fruits and the behaviour of implementing vegetable and fruit consumption with nutritional status in Bhayangkara University Bekasi Students. Method: This study used a cross sectional design method on 61 students of the Faculty of Communication Sciences at Bhayangkara University Bekasi. Sampling of this study using consecutive sampling method. Data collection includes nutritional knowledge of vegetables and fruits and behaviour measured using the Food Frequency Questioner (FFQ) questionnaire. Data were analyzed using the Chi-Square test. Results: The results of bivariate analysis using the Chi-Square test show that there is no significant relationship between nutritional knowledge and nutritional status (p-value = 0.153) and there is a significant relationship between the behaviour of implementing vegetable and fruit consumption with nutritional status (p-value = 0.011) in Bhayangkara University Bekasi students. Conclusion: There is no relationship between nutritional knowledge and nutritional status and there is relationship between the behaviour of implementing vegetable and fruit consumption with nutritional status in students of Bhayangkara University Bekasi.